Anniversaries - Vilnensia, Acta Paedagogica (Acta Paedagogica Vilnensia, 2010)
Jonas Dautaras. Fosterer of a Child’s Independent PersonalityLeonas Jovaiša. New Education Systems from Education Historian ViewOna Danutė Žilienė. Humanism as a Scientific Guideline